2006
DOI: 10.1007/s10346-006-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic rockslide-debris avalanche at St. Bernard, Southern Leyte, Philippines

Abstract: On 17 February 2006, a rockslide-debris avalanche cascaded down the steep slope of Mt. Can-abag, burying the entire village of Guinsaugon in St. Bernard, Southern Leyte, Philippines.Casualties include 139 dead with 980 still missing and presumed dead, making it perhaps the most catastrophic landslide in Philippine history. The landslide started at the ridge top along a fault plane associated with the active Philippine Fault Zone. It started as a block slide that transformed into an avalanche. The entire event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Figure 5 shows the relationship between the landslide surface features and the subsurface fault structure. Field observations by Catane et al (2006) confirmed the presence of an active fault-related zone of highly fractured and sheared materials from the top of the ridge down to its base. These structures are important preparatory factors for the landslide.…”
Section: Results and Interpretationmentioning
confidence: 81%
See 2 more Smart Citations
“…Figure 5 shows the relationship between the landslide surface features and the subsurface fault structure. Field observations by Catane et al (2006) confirmed the presence of an active fault-related zone of highly fractured and sheared materials from the top of the ridge down to its base. These structures are important preparatory factors for the landslide.…”
Section: Results and Interpretationmentioning
confidence: 81%
“…Witnesses had also observed several minor events before 17 February, such as the occurrence of small rock falls a few days before the major landslide and the distinct siltation of a stream leading to Guinsaugon one day before the catastrophic event. Catane et al (2006) (Fig. 2).…”
Section: Chronology Of the Landslide Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area is part of the Southern Leyte segment of the sinistral PFZ, which has an average movement of 0.55 cm yr −1 (Cole et al, 1989) up to 3.5 cm yr −1 (Duquesnoy, 1997, as cited by Catane et al, 2006). This has led to formation of regional discontinuities and development of thick clay-rich gouge zones in the surface prominent in the en- tire province and other locations along the PFZ (Hart et al, 2002).…”
Section: Geotechnical Considerationmentioning
confidence: 99%
“…The topmost contributing slope of the Guinsaugon landslide is 50 to 60 • (Catane et al, 2006) with a post-landslide configuration of the crown exhibiting a distinct four-slip-plane failure. Based on the observed orientation of discontinuities and immense pore pressure developed from accumulated rainfall, a combined wedge, toppling, and planar slide is believed to have caused gravitational failure at Guinsaugon (Catane et al, 2008).…”
Section: Failure Mechanismmentioning
confidence: 99%